2007
DOI: 10.1590/s0100-69162007000100022
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade e qualidade de cana-de-açúcar cultivada em solo tratado com lodo de esgoto, vinhaça e adubos minerais

Abstract: RESUMO: O uso agrícola de resíduos orgânicos, de origem agrícola, urbana ou industrial, é uma interessante alternativa de disposição, permitindo a reciclagem de nutrientes (NPK) nos ecossistemas. Este trabalho avaliou o efeito da aplicação de lodo de esgoto como fonte de N e de vinhaça como fonte de K comparado ao uso de fontes minerais desses nutrientes sobre a produtividade e variáveis agroindustriais da cana-de-açúcar, por dois anos consecutivos (cana-planta e cana-soca). O experimento foi conduzido em Lato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
14

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 1 publication
2
10
0
14
Order By: Relevance
“…The high percent difference observed mainly in the ratoon cane is about twice as high as that observed in the plant cane, which demonstrates the importance of irrigation and its relevant effect, especially in ratoon cane, to obtain higher yields and, therefore, promote greater economic return. Increases in the concentration of sucrose in the juice have been observed in the irrigated cultivation of sugarcane (Dantas Neto et al, 2006;Tasso Júnior et al, 2007;Singh et al, 2007;Barbosa et al, 2012;.…”
Section: Resultsmentioning
confidence: 99%
“…The high percent difference observed mainly in the ratoon cane is about twice as high as that observed in the plant cane, which demonstrates the importance of irrigation and its relevant effect, especially in ratoon cane, to obtain higher yields and, therefore, promote greater economic return. Increases in the concentration of sucrose in the juice have been observed in the irrigated cultivation of sugarcane (Dantas Neto et al, 2006;Tasso Júnior et al, 2007;Singh et al, 2007;Barbosa et al, 2012;.…”
Section: Resultsmentioning
confidence: 99%
“…Giachini & Ferraz (2009) indicam que a resposta da produtividade de colmos é mais intensa em solos de menor fertilidade. Tasso Júnior et al (2007) registraram, trabalhando com vinhaça em Latossolo Vermelho distroférrico, que na cana planta a vinhaça não apresentou efeito na produtividade enquanto na cana soca (1ª soca) houve diferença nos incrementos da produção de colmos.…”
Section: Resultsunclassified
“…Silva et al (2007) alertam que, quando aplicada em altas doses, pode acarretar efeitos indesejáveis como o comprometimento da qualidade da cana para produção de açúcar, salinização do solo e poluição do lençol freático. Silva et al (2006) verificaram efeito da vinhaça na matéria seca das raízes da cana-de-açúcar, fato este atribuído às melhores condições químicas do solo, pela aplicação deste subproduto.…”
Section: Introductionunclassified
“…In this case the maximum fiber content (14.85 %) was obtained without sludge application and the minimum (13.90 %) at a sludge dose of 10.8 t ha -1 . Fiber levels of 10 -11 % were obtained by Tasso Júnior et al (2007), evaluating the sludge application on cane cultivar SP 81-3250.…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have reported on sludge application to sugarcane (Oliveira, 2000;Silva et al, 2001;Camilotti et al, 2006;Marques et al, 2007;Tasso Júnior et al, 2007;Chiba et at., 2008Chiba et at., , 2009), but most of them focused on doses above those permitted by the technical criteria of Resolution 375 of 2006, issued by the National Environmental Council (CONAMA, 2006), the document that regulates the agricultural use of sewage sludge in Brazil. There are very few studies on the effects of agronomic sludge rates on sugarcane yield.…”
Section: Introductionmentioning
confidence: 99%